STUDY OF ALTERNATIVES FOR PRODUCING TORULA YEAST FROM VARIOUS SUBSTRATES - Fuentes Ramírez, Lirianet; Mutis Silveira, Christian Manuel; Cabrera Estrada, Isabel; Cortés Falcón, Mariano F. (Centro Azúcar Journal, 2026)
Introduction: The use of sugarcane by-products in animal feed to increase the added value of sugarcane is one of the alternatives that has been considered most viable and attractive in the short term Objective: To determine the technical and economic possibilities during the extraction of juice from mill filters, final molasses, and distillery vinasse for the production of Torula yeast. Materials and Methods: Mass and energy balances were carried out at different stages of the Torula yeast production procces, as well as analyses of alternative mixtures with different proportions of filter juice and final molasses to supply the distillery, and the use of final molasses in conjunction with vinasse for Torula yeast production. Investment and production costs were also evaluated using updated cost indices and the application of the six-tenths rule. Results and Discussion: It is evident that the use of filter juice in combination with final molasses reduces ethanol production costs and ensures the supply of substrates for Torula yeast production. It was also verified that surplus bagasse can be used as an energy source in the distillery. Conclusions: The installation of a Torula yeast plant at the agroindustrial company Melanio Hernández is technically viable and economically feasible, yielding a Net Present Value (NPV) of 9.3 million USD, with an Internal Rate of Return (IRR) of 9% and a discounted payback period of 7 years.